Investigations into transcription and transcripts in Saccharomyces cerevisiae - Fischl, H (2015)
Transcription of the Saccharomyces cerevisiae genome by RNA polymerase II (Pol II) is pervasive, occurring on the sense and antisense strands of protein-coding genes and at intergenic regions. Factors associate with Pol II at particular positions along transcribed regions (transcription units (TUs)) with functions including facilitating the transition of Pol II through chromatin, controlling termination and processing the nascent transcript. By developing a new technique, these associations were mapped strand-specifically with nucleotide resolution. This revealed increased transitions in the binding of factors along TUs, periodic binding as Pol II transcribes through nucleosomes and differential binding of particular factors to particular types of TU. These associations are regulated to influence the stability and subcellular location of the transcripts produced. Analysis of transcription levels upon a change in conditions showed widespread and rapid changes resulting from changes in the proportion of cells in particular phases of the yeast metabolic cycle. At individual loci, clustered TUs showed reciprocal changes in transcription. Overlap between coding and non-coding TUs on both strands was shown to regulate these changes, repressing out of phase transcription. While the process of non-coding transcription is generally thought to be the regulatory agent, a role for non-coding transcripts should not be overlooked. Non-coding RNAs were shown to be able to bind double-stranded DNA sequence-specifically at several locations providing a mechanism by which these RNAs could interact with chromatin and mediate a function.